Ressoador retangular defenda com quatro camadas fotônicas - Andrade, Humberto Dionísio de (2010)
Recently, planar antennas have attracted interest due to its characteristics as well as the advantages they offer compared to other types of antennas. In the area of mobile communications the need for such antennas has become increasingly intense due to development, which requires antennas that operate in multifrequency and broadband. The microstrip antennas have narrow bandwidth due to losses in the dielectric caused by irradiation. Another limitation is the radiation pattern degradation due to generation of surface waves in the substrate. Some techniques are being developed to minimize this bandwidth limitation, as is the case in the study of type materials PBG - Photonic Band Gap, to compose the dielectric material. The analysis developed in this work were performed with use of the method LTT - Transverse Transmission Line, in the field of Fourier transform that uses a component propagating in the y direction (transerve real direction of propagation z), thus treating the general equations of the fields electric and magnetic fields as a functions of y E and Hy . This work has as main objective the method LTT structures resonator line slot with four layers of material photonic PBG, for obtaining the complex resonant frequency and efficiency of this structure. PBG theory is applied to obtain the relative permittivity for the substrate biases sep compounds photonic material. Numerical-computational results in graph form in two dimensions for all the analysis are presented for the proposed structures that have photonic materials, as substrates